(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article studies scientific views on the orthoepic norms of the French language and gives a reaction to them. The concepts of plurisystem and grapheme are also given, as well as principles that allow us to describe the French spelling system.